The Dual Distal Demonstrative in Modern Standard Arabic: Between Norms and Non-Canonicity - Michalski, Marcin (Lingua Posnaniensis, 2012)
The system of the demonstrative pronouns in Classical Arabic (CA), on which that of Modern Standard Arabic (MSA) is based, is distance-oriented and has been described as a two-term (proximal-distal) or three-term (proximal-medial-distal) system. A characteristic feature of the subsystem of the distal demonstratives in CA was that it had a suffix indicating the gender and number of the addressee(s). Within the subsystem of distal demonstratives, the dual form has not been described in a unanimous way: authors do not agree as to its form, some give more than one, others do not mention the issue, while according to some descriptions this form does not exist at all. In MSA texts, the function of the dual distal demonstrative is, however, sometimes carried out by a form which according to CA rules should be used when a singular object is pointed to and two persons are being addressed. This means that some users of MSA have reinterpreted the CA indicator of a dual addressee, -kumā, as the indicator of the duality of the object pointed to.